2020
DOI: 10.1088/1361-6463/aba64d
|View full text |Cite
|
Sign up to set email alerts
|

Formation and control of the E2∗ center in implanted β-Ga 2 O 3 by reverse-bias and zero-bias annealing

Abstract: Deep-level transient spectroscopy measurements are conducted on β-Ga 2 O 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 43 publications
(80 reference statements)
5
18
0
Order By: Relevance
“…Furthermore, the calculated O-D stretch modes of D-containing unshifted V Ga1 and V Ga2 defects should be polarized along the [010] lattice vector 26,27,35 showed that H trapping and relaxation processes in β -Ga 2 O 3 make it highly unlikely that any of the hydrogenated unshifted V Ga will occur. 35 Interestingly, recent experimental 16 and theoretical work 19 have suggested that V Ga -V O divacancy complexes could give rise to the so-called E2* level observed using DLTS in β -Ga 2 O 3 single crystals after H-and He-irradiation. Importantly, the positron annihilation signature of a cation vacancy is expected to remain relatively unchanged compared to its complex with a small anion vacancy 25,36 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the calculated O-D stretch modes of D-containing unshifted V Ga1 and V Ga2 defects should be polarized along the [010] lattice vector 26,27,35 showed that H trapping and relaxation processes in β -Ga 2 O 3 make it highly unlikely that any of the hydrogenated unshifted V Ga will occur. 35 Interestingly, recent experimental 16 and theoretical work 19 have suggested that V Ga -V O divacancy complexes could give rise to the so-called E2* level observed using DLTS in β -Ga 2 O 3 single crystals after H-and He-irradiation. Importantly, the positron annihilation signature of a cation vacancy is expected to remain relatively unchanged compared to its complex with a small anion vacancy 25,36 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies utilizing deep-level transient spectroscopy (DLTS) have shown that irradiation also gives rise to two charge state transition levels labeled E2* and E4. 4,[14][15][16] Annealing the samples at 600 K removes the E4 level but also increases the concentration of E2*. 4 In fact, E2* has been shown limit a) Electronic mail: antti.j.karjalainen@iki.fi the performance β -Ga 2 O 3 -based metal-semiconductor field effect (MESFET) transistors 17,18 and suggested to originate from V Ga -V O divacancy defect complexes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the authors of this article reported on the formation of E * 2 in β-Ga 2 O 3 subjected to H and/or He implantation, as measured by DLTS on Schottky barrier diodes. It was found that the introduction of E * 2 is promoted when performing a subsequent annealing * ymirkf@fys.uio.no at 650 K under an applied reverse-bias voltage (reverse-bias annealing) [8]. Conversely, heat treatments without an applied reverse-bias voltage (zero-bias annealing) lead to a decrease in the E * 2 concentration, which is more pronounced in the presence of H. Moreover, simulations of DLTS spectra suggest that E * 2 consists of several overlapping signatures [8].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the introduction of E * 2 is promoted when performing a subsequent annealing * ymirkf@fys.uio.no at 650 K under an applied reverse-bias voltage (reverse-bias annealing) [8]. Conversely, heat treatments without an applied reverse-bias voltage (zero-bias annealing) lead to a decrease in the E * 2 concentration, which is more pronounced in the presence of H. Moreover, simulations of DLTS spectra suggest that E * 2 consists of several overlapping signatures [8]. Based on these experimental results, it was proposed that the most likely origin of E * 2 is a defect complex involving intrinsic defects, which can interact with H donors, and exist in several different configurations, where the configurations giving rise to E * 2 are more likely to form when the Fermi level is shifted away from the conduction band minimum (CBM), i.e., in the space-charge region of Schottky barrier diodes.…”
Section: Introductionmentioning
confidence: 99%